FERMI DETECTION DELAYED GeV EMISSION FROM THE SHORT GAMMA-RAY BURST 081024B - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Asano, K.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2010)
We report on the detailed analysis of the high-energy extended emission from the short gamma-ray burst (GRB) 081024B detected by the Fermi Gamma-ray Space Telescope. Historically, this represents the first clear detection of temporal extended emission from a short GRB. The light curve observed by the Fermi Gamma-ray Burst Monitor lasts approximately 0.8 s whereas the emission in the Fermi Large Area Telescope lasts for about 3 s. Evidence of longer lasting high-energy emission associated with long bursts has been already reported by previous experiments. Our observations, together with the earlier reported study of the bright short GRB 090510, indicate similarities in the high-energy emission of short and long GRBs and open the path to new interpretations.
CRIS-Team WoS Importer:2020-01-15